New Perspectives for Resistance to PARP Inhibitors in Triple-Negative Breast Cancer - Han, Ye; Yu, Xiaopeng; Li, Shuqiang; Tian, Ye; Liu, Caigang (Frontiers in Oncology, 2020)
Poly (ADP-ribose) polymerase (PARP) inhibitors are a therapeutic milestone exerting a synthetic lethal effect in the treatment of cancer involving BRCA1/2 mutation. Theoretically, PARP inhibitors (PARPi) eliminate tumor cells by disrupting DNA damage repair through either PARylation or the homologous recombination (HR) pathway. However, resistance to PARPi greatly hinders therapeutic effectiveness in triple-negative breast cancer (TNBC). Owing to the high heterogeneity and few genetic targets in TNBC, there has been limited therapeutic progress in the past decades. In view of this, there is a need to circumvent resistance to PARPi and develop potential treatment strategies for TNBC. We present, herein, a review of the scientific progress and explore the mechanisms underlying PARPi resistance in TNBC. The complicated mechanisms of PARPi resistance, including drug exporter formation, loss of poly (ADP-ribose) glycohydrolase (PARG), HR reactivation, and restoration of replication fork stability, are discussed in detail in this review. Additionally, we also discuss new combination therapies with PARPi that can improve the clinical response in TNBC. The new perspectives for PARPi bring novel challenges and opportunities to overcome PARPi resistance in breast cancer.